Pergeseran Identitas Budaya Komunitas Supporter Surabaya di Instagram - Ririn Puspita Tutiasri; Ade Kusuma (Universitas Muhammadiyah Sidoarjo, 2017)
Bonek is called to support the football team Persebaya Surabaya. Bonek image could not be separated from the abbreviation of the word itself, namely